PENGARUH DANA PIHAK KETIGA (DPK), MODAL INTI, DAN BAGI HASIL TERHADAP PEMBIAYAAN PADA BANK UMUM SYARIAH DI INDONESIA (PERIODE 2014 -2021) - Ismuadi Ismuadi; Zaki Fuad; Muliana Rahmah (Prodi Perbankan Syariah FEBI UIN Ar-Raniry, 2022)
Abstract This study aims to look at the Effect of Third Party Funds (DPK), Core Capital, and Profit Sharing on Financing in Islamic Commercial Banks in Indonesia (2014-2021 Period). This data uses secondary data in the form of documentation with its processing using SPSS 25. The analytical method used is multiple linear analysis techniques. The results showed that third party funds (DPK), core capital, and profit sharing had a positive effect on the amount of financing